Women's birthing bodies and the law : unauthorised intimate examinations, power, and vulnerability - Pickles, Camilla; Herring, Jonathan (Oxford, UK ; Hart Publishing, an imprint of Bloomsbury Publishing, 2020)
"This is the first book to unpack the legal and ethical issues surrounding unauthorised intimate examinations during labour. The book uses feminist, socio-legal and philosophical tools to explore the issues of power, vulnerability and autonomy. The collection challenges the perception that the law adequately addresses different manifestations of unauthorised medical touch through the lens of women's experiences of unauthorised vaginal examinations during labour. The book unearths several broader themes that are of huge significance to lawyers and healthcare professionals such as the legal status of women and their bodies. The book raises questions about women's experiences during childbirth in hospital settings. It explores the status of women's bodies during labour and childbirth where too easily they become objectified, and it raises important issues around consent. The book highlights links to the law on sexual offences and women's loss of power under the medical gaze. The book includes contributions from leading feminist philosophers, medical professionals, and academics in medicine and law, and offers pioneering analysis relevant to lawyers and healthcare professionals with an interest in medical law and ethics; feminist theory; criminal law; tort law; and human rights law"--
Introduction / Camilla Pickles and Jonathan Herring -- Non-consented vaginal examinations : the birthrights and AIMS perspective / Rebecca Brione -- Silence, acquiescence or consent : interpreting women's responses to intimate examinations / Elsa Montgomery -- Female genital examination and autonomy in medicine / Neda Taghinejadi and Brenda Kelly -- When a uterus enters the room, reason goes out the window / Stella Villarmea -- Human rights and gender stereotypes in childbirth / Christina Zampas -- How should the performance of periparturient vaginal examinations be regulated? / Charles Foster -- Including the victim's perspective : can vaginal examinations ever be sexual assaults? / Catarina Sjölin -- When 'battery' is not enough : exposing the gaps in unauthorised vaginal examinations during labour as a crime of battery / Camilla Pickles -- Implied consent and vaginal examination in pregnancy / Jonathan Herring -- Troubling consent : pain and pressure in labour and childbirth / Claire Murray -- Redressing unauthorised vaginal examinations through litigation / Andrea Mulligan.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Informed consent (Medical law); Pregnant women -- Legal status, laws, etc; Medical examinations; Obstetrics -- Law and legislation; Physician and patient; Childbirth; Medical & healthcare law; Electronic books